PROTOTYPE ALAT PEMBERSIH UDARA DARI DEBU DAN ASAP ROKOK DI RUANGAN BERBASIS LOGIKA FUZZY DENGAN SISTEM NOTIFIKASI ALARM - Mentari, Ega Julia; Fitriani, Endah (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2025)
The problem of air pollution is one of the negative health impacts that occur in society. The high level of population allows active smokers to increase. This is also exacerbated by the growing development of buildings which causes a reduction in green space that functions as a filter for dirty air. To keep the air clean, several efforts are made such as planting trees outdoors and using air filters for indoors. This research is made to create a design tool that will be a detector for the presence of cigarette smoke and will suction the air if smoke and dust are detected. With the use of the NodeMCU ESP8266 microcontroller as a G2y1010 dust sensor data reader, MQ-135 gas sensor and DHT 22 temperature sensor which will process inputs and produce outputs based on fuzzy logic control rules. Equipped with a room fragrance after the filtering process is complete as a complement to the comfort process in the room.In addition, an alarm notification system will also be raised as a warning if cigarette smoke is detected.Keywords: automatic system, water truck, ultrasonic sensor, infrared sensor, air filling efficiency